Representation of Local Cultural Wisdom in the Kuta Beach Mini Festival in the Kuta Badung Traditional Village - Wirata, I Nengah; Mahardika, Made Chossya Wira (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: This article aims to revive local cultural wisdom in the Kuta Traditional Village which has been eroded by the influence of globalization Research methods: This research uses an interpretive qualitative approach by collecting data through field observations, interviews and literature reviews Results and discussion: The Kuta Beach Mini Festival is able to create a space for the people of Kuta Badung Traditional Village to strengthen their sense of cultural identity, through dance, music, fine arts and various traditional activities and revive cultural elements that are in danger of being forgotten. Implication: This article has substantial cultural implications by illustrating how the representation of local cultural wisdom in festivals can influence cultural preservation, revolution, and understanding.